2009
DOI: 10.1007/s10562-009-0057-1
|View full text |Cite
|
Sign up to set email alerts
|

Propane Oxidative Dehydrogenation Over Ln–Mg–Al–O Catalysts (Ln = Ce, Sm, Dy, Yb)

Abstract: Ln-Mg-Al mixed oxide catalysts (Ln = Ce, Sm, Dy, Yb) were prepared from layered double hydroxide precursors, characterized using XRD, N 2 adsorption, TG-DTG, EDX, H 2 -TPR and CO 2 -TPD techniques and tested in the oxidative dehydrogenation of propane in the temperature range 450-600°C. For all the catalysts the conversion increases with increasing the reaction temperature while the propene selectivity decreases to the benefit of carbon oxides for Ce-based system and of cracking products for the others. The be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…No significant reaction took place in the absence of catalysts [45]. For all the VO x /SBA-15 samples, the main products were propene and carbon oxides, with minor amounts of cracking products (methane and ethylene) and trace amounts of oxygenates.…”
Section: Catalytic Studymentioning
confidence: 94%
“…No significant reaction took place in the absence of catalysts [45]. For all the VO x /SBA-15 samples, the main products were propene and carbon oxides, with minor amounts of cracking products (methane and ethylene) and trace amounts of oxygenates.…”
Section: Catalytic Studymentioning
confidence: 94%
“…The results showed that Ce promotion mainly contributed to the formation of tetrahedrally coordinated copper species, which favored the enhancement of the total alcohol selectivity. Mitran et al prepared LnMgAl mixed oxide catalysts (Ln = Ce, Sm, Dy, Yb) from LDH precursors and tested them in the oxidative dehydrogenation of propane (Mitran et al, 2009). The best yields of propene were obtained with Dy and Sm promoted catalysts.…”
Section: Catalytic Activitymentioning
confidence: 99%
“…The Cu 20 PMO catalyst used in the earlier studies was prepared by calcining 3:1 Mg 2+ :Al 3+ hydrotalcite (HTC) in which 20% of the Mg 2+ was replaced by Cu 2+ . HTCs can be readily modified by doping with other M 2+ and/or M 3+ ions, and such HTC-derived PMOs are solid bases that can catalyze the transesterification of triglyceride esters and absorb atmospheric CO 2 . Furthermore, we have speculated that deprotonation activates the phenolic intermediates of lignin disassembly toward secondary reactions; thus, it may be possible to enhance selectivity and/or reactivity by modifying the PMO support or by adding Brønsted or Lewis acids to the reaction medium.…”
Section: Introductionmentioning
confidence: 99%